Implementation of the Time Game Tournament (TGT) Model in Improving Student Learning in PAI Subjects (Grade VII Studies at YPI Middle School, Deli Tua District, Deli Serdang, North Sumatra) - Adelia (Getpress Management Journals, 2023)
A learning process is said to be successful if the teacher is able to use learning methods appropriately. Along with the renewal of the education curriculum, the 2013 curriculum requires the activeness of students. Teachers are required to have the ability to master various teaching models used to achieve the desired learning objectives, one of which is the Teams Games Tournament (TGT) model. This article aims to explain how the effect of using the Teams Games Tournament (TGT) type cooperative learning model can improve the learning outcomes of Islamic Religious Education of seventh grade students of YPI Deli Tua Junior High School. The method used in this article is classroom action research (PTK). Classroom action research is an observation of learning activities in the form of an action, which is deliberately raised and occurs in a class together. Based on the results of the analysis that the researchers have done, the use of the Teams Games Tournament (TGT) method can improve the learning outcomes of class VII students of YPI Deli Tua Junior High School in the 2023/2024 academic year. The completeness of student learning outcomes in cycle I was 43.75%, and in cycle II it was 81.25%. The increase in completeness of learning outcomes was 37.5%. On the theme of Closer to Allah SWT Which is Very Beautiful His Name.